Environmentally Friendly Based Educative Game Development Training For Teachers Early Childhood Education Programs - Kusmiyati Kusmiyati; Ni Nyoman Sarmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2020)
This community service aims at developing Educative Game Tools (EGT) based environmentally friendly. This activity is motivated by the fact that many PAUD (Early Childhood Education) teachers are not PGPAUD graduates and even high school graduates. There is still a lack of understanding and skills of early childhood teachers in designing and making educational teaching aids environmentally friendly. Besides that, their motivation to design their own Educational Game Tools is still low. Based on the above problems, the solution offered is to provide training for PAUD teachers in Wonokromo village to understand, design, and create their own innovative and Educative Game Tools (EGT) based environmentally friendly. The program target is for PAUD teachers to know, understand the importance of EGT in PAUD learning and design creative and innovative EGT. The concept of EGT is oriented towards safe for children, environmentally friendly, and source of used materials that are quickly processed from the surrounding environment. As a result, all participants gained knowledge and skills in designing EGT to improve quality and professionalism as Early Childhood Education teachers.